2008
DOI: 10.1007/s11626-008-9111-3
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro model to assess mechanisms and efficacy of a cellular conduit for treatment of avascular meniscal injuries

Abstract: Tears in the avascular portion of the knee meniscus are commonplace and are frequently incapable of healing spontaneously. Delivery of synovial cells from the meniscal periphery to avascular injuries can result in an effective healing response but is difficult to accomplish surgically. This report describes the development of a novel in vitro model comprised of three-dimensionally cultured cells in agarose used to assess the proof of concept that a cellular conduit device could be used to facilitate the delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…In addition, the synovial membrane is considered to include multipotent cells that contribute to tissue regeneration after injury 3 . It is reported that cells migrate from the synovial membrane after meniscal injury to regenerate the damaged tissue 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the synovial membrane is considered to include multipotent cells that contribute to tissue regeneration after injury 3 . It is reported that cells migrate from the synovial membrane after meniscal injury to regenerate the damaged tissue 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Current meniscal TE efforts have focused on the repair of focal defects through the use of stem cells [5, 6] and scaffold materials [7, 8]. There have also been efforts to characterize the behavior of meniscal fibrochondrocytes and how these cells generate extracellular matrix (ECM) in scaffolds with simple geometry, including agarose [9], alginate [10], chitosan-graft-poly(N-isopropylacrylamide) [11], ploy (ε-caprolactone) [12], polyglycolic acid (PGA) [9], polyethylene terephthalate [13], and poly(L -lactic acid) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Other reports, however, document the deformation and subsequent closure of trephination holes resulting from meniscal viscoelasticity resulting in inconsistent neovascularization [40]. Recently, synthetic conduits implanted within fashioned trephinations were assessed in both animal and in vitro models, which demonstrated optimized maintenance of the channel diameter, thus facilitating neovascularization and conduction of synoviocytes more optimally than with the presence of a trephine alone [18,33].…”
Section: Current Meniscal Treatment Modalitiesmentioning
confidence: 99%